Using gene expression information to provide insights into patterning and differentiation - Stathopoulos, Angelike (Henry Stewart Talks, 2008)
Gastrulation, Dorsoventral patterning in the early embryo, Activation of signaling pathways, Control of cell movements and differentiation events, Mesoderm cell spreading and heart cell specification, FGF signaling during development
Archived at 2018/06/07